1998
DOI: 10.1021/ja973761j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Interchain Interactions on the Absorption and Luminescence of Conjugated Oligomers and Polymers:  A Quantum-Chemical Characterization

Abstract: Correlated quantum-chemical calculations are used to investigate the influence of interchain interactions on the absorption and emission of π-conjugated chains. The results are discussed in relation to the utilization of conjugated materials as active elements in electro-optic devices; they provide guidelines on how to prevent a substantial decrease in luminescence yield in solid films. In high-symmetry cofacial configurations, interchain interactions lead to a blue shift of the lowest optical transition compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
489
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 590 publications
(535 citation statements)
references
References 70 publications
42
489
0
1
Order By: Relevance
“…In the few regions where the interfacial emission shows the solvatochromic red shift, the fact that the excited state has a large dipole moment (∼9-13 D larger than that of the ground state) suggests strong excited-state charge separation. Because typical interchain distances in conjugated polymer films are ∼4 Å, 66 this magnitude of ∆µ e suggests nearly complete separation of unit charges between adjacent chains if the radius of the emitter R ) 5 Å, consistent with assignment to interchain polaron pairs. 6 This same dipole moment could be achieved for larger choices of the radius of the emitter if only fractional charges were separated, which still would be suggestive of interchain species comprised of highly charge-asymmetric exciplexes.…”
Section: B Continuum Electrostatic Modeling Of Meh-ppv Interfacial Ssupporting
confidence: 64%
“…In the few regions where the interfacial emission shows the solvatochromic red shift, the fact that the excited state has a large dipole moment (∼9-13 D larger than that of the ground state) suggests strong excited-state charge separation. Because typical interchain distances in conjugated polymer films are ∼4 Å, 66 this magnitude of ∆µ e suggests nearly complete separation of unit charges between adjacent chains if the radius of the emitter R ) 5 Å, consistent with assignment to interchain polaron pairs. 6 This same dipole moment could be achieved for larger choices of the radius of the emitter if only fractional charges were separated, which still would be suggestive of interchain species comprised of highly charge-asymmetric exciplexes.…”
Section: B Continuum Electrostatic Modeling Of Meh-ppv Interfacial Ssupporting
confidence: 64%
“…When the conjugation length is longer than the intermolecular separation, as is generally the case in polymers, quantumchemical calculations have shown that the exciton bandwidth decreases as the conjugation length increases. 1,46,47 This is because for long conjugation lengths the point dipole approximation breaks down and there is a tendency for positive and negative contributions to the atomic transition densities to cancel each other, leading to a reduction of the interaction energy/exciton bandwidth. Within this model we can now interpret the subtle variations in the absorption spectra as a function of MW in terms of variations of the intrachain conjugation length.…”
Section: Spectroscopic Characterizationmentioning
confidence: 99%
“…The existence of an A g state or a triplet excited state below the 1B u state will favor nonradiative recombination (in both cases, direct radiative transitions to the ground state are forbidden). Interchain interactions in the excited state (''excimers'') also lead to nonradiative channels for decay (Jenekhe and Osaheni, 1994;Rothberg et al, 1996;Cornil et al, 1998).…”
Section: Photodopingmentioning
confidence: 99%